Pleiotropic effects of niacin: Current possibilities for its clinical use - Zeman Miroslav; Vecka Marek; Perlík František; Staňková Barbora; Hromádka Robert; Tvrzická Eva; Širc Jakub; Hrib Jakub; Žák Aleš (Acta Pharmaceutica, 2016)
Niacin was the first hypolipidemic drug to significantly reduce both major cardiovascular events and mortality in patients with cardiovascular disease. Niacin favorably influences all lipoprotein classes, including lipoprotein[a],and belongs to the most potent hypolipidemic drugs for increasing HDL-C. Moreover, niacin causes favorable changes to the qualitative composition of lipoprotein HDL. In addition to its pronounced hypolipidemic action, niacin exerts many other, non-hypolipidemic effects (e.g., antioxidative, anti-inflammatory, antithrombotic), which favorably influence the development and progression of atherosclerosis. These effects are dependent on activation of the specific receptor HCA2. Recent results published by the two large clinical studies, AIM-HIGH and HPS2-THRIVE, have led to the impugnation of niacin’s role in future clinical practice. However, due to several methodological flaws in the AIM-HIGH and HPS2-THRIVE studies, the pleiotropic effects of niacin now deserve thorough evaluation. This review summarizes the present and possible future use of niacin in clinical practice in light of its newly recognized pleiotropic effects.